OP44 Feeding difficulties and maternal concerns at age 3 years are associated with a decline in children's diet quality to age 6. (2nd September 2017) - Jarman, M; Robinson, SM; Lawrence, WT; Barker, ME; Godfrey, KM; Cooper, C; Inskip, HM; Baird, J
Abstract : Background: Cross-sectional studies show that picky eating behaviours in young children are associated with poorer quality diets. Limited longitudinal research explores whether these effects persist until later childhood. We assessed feeding difficulties and eating behaviours at age 3 years and their influence on quality of diet at age 3 and 6. Methods: The Southampton Women's Survey is a prospective cohort study of women pre-pregnancy, those that became pregnant and their children. Complete data for this analysis were available on 1946 mother-child pairs. When children were age 3 years, mothers completed a questionnaire assessing frequency of feeding difficulties, and concerns about specific eating behaviours in three categories indicating the level of the problem. Diet was assessed using a food frequency questionnaire. Principal components analysis was used to examine dietary patterns; a z-score was derived with higher scores reflecting a better quality of diet. Dietary assessment was repeated at age 6 years. Linear regression models were used to assess associations between feeding difficulties, concerns about eating behaviours and diet scores at age 3 and 6. Models were adjusted for maternal age, education and number of children, and interactions between feeding difficulties and maternal concern about eating behaviours were assessed. Results: At age 3 more frequent feeding difficulties were associated with poorer quality diets [β −0.14 SD/category (95% CI −0.18, –0.09)]. Greater maternal concern about the eating behaviours 'my child refused to eat the right foods' and 'my child has been choosy with food' was associated with poorer quality diet at age 3 [β −0.33 SD/category (95% CI −0.43, –0.23) and β −0.20 SD/category (95% CI −0.31, –0.09), respectively] compared to children whose mothers were less concerned. These associations remained at age 6, even after adjustment for diet score at age 3, suggesting that greater maternal concern about their child 'refusing to eat the right foods' and 'being choosy with food' was associated with a worsening of children's diet quality to age 6 [β −0.13 SD/category (95% CI −0.23, –0.04) and β −0.16 SD/category (95% CI −0.27, –0.05), respectively]. Conclusion: These findings suggest that the way mothers respond to their child's eating behaviours at age 3 might influence a decline in children's quality of diet until age 6. Heightened maternal concern may generate a negative feeding environment which exacerbates picky eating behaviours in young children. Family support during preschool years for managing eating behaviours could contribute to more optimal diets in early childhood.